552The lung function and airway inflammation markers associated with short-term pollen exposure- A systematic review. (2nd September 2021) - Idrose, N. Sabrina; Lodge, Caroline; Koplin, Jennifer; Vicendese, Don; Douglass, Jo; Dharmage, Shyamali
Abstract: Background: Experimental challenge studies have shown that pollen can affect the lungs and airways. Here, we systematically reviewed community-based studies investigating outdoor pollen exposure, lung function and/or airway inflammation. Methods: Four online databases were searched. The search strategy included terms relating to both exposure and outcomes. Inclusion criteria were studies published in English that were representative of the community. We only considered cross-sectional or short-term longitudinal studies which investigated pollen exposure by levels or season. Study quality assessment was performed using the Newcastle-Ottawa scale. Meta-analysis was conducted using random-effects models. Results: We included 27 of 6, 551 studies identified from the search. Qualitative synthesis indicated associations between pollen exposure and predominantly type-2 inflammation in both the upper and lower airways, but little evidence for lung function changes. People with ever asthma and/or seasonal allergic rhinitis (SAR) were at higher risk of such airway inflammation. Meta-analysis confirmed a positive relationship between pollen season and eosinophilic airway inflammation in people with ever SAR but the results between studies were highly variable. Heterogeneity was reduced after further subgrouping by age and the forest plots indicated that eosinophilic airway inflammation to outdoor pollen exposure increased with age. Conclusion: Among people with ever asthma and ever SAR, exposure to increased ambient pollen triggers type-2 airway inflammation rather than a non-specific or innate inflammation. Key messages: This review indicates pollen exposure influences predominantly type-2 airway inflammation, but little evidence on lung function.